Supervisi Individual yang Kontinyu untuk Meningkatkan Kemampuan Mengelola Pembelajaran Guru Mata Pelajaran di SMAN 2 Pujut - Lalu Sahbin (UNDIKMA, 2021)
The purpose of this research is to improve the ability to manage the learning of subject teachers through continuous individual supervision. The research method used is school action research which consists of two cycles, each cycle consisting of planning, implementation, observation and reflection stages. Data collection techniques using documentation, observation and checklists. The data analysis technique in this study used descriptive analysis. The results of this study indicate that the classroom management competence of subject teachers increases from cycle to cycle, in the pre-cycle the average value of the pedagogic competence of 15 teachers is 80%. In the first cycle the number of teachers who made the syllabus and lesson plans was 33% and 27%, in the second cycle there was an increase in the number of teachers' syllabus and lesson plans by 80% and 87%, while the competence of teachers in compiling the syllabus and lesson plans increased to 87%. Thus, through individual supervision, subject teachers can improve the ability to manage learning.